Treatment Approaches for COVID-19: A Critical Review - Sodum, Nalini; Kumar, Gautam; Rao, Vanishree; Kumar, Nitesh; Rao, Chamallamudi M. (Mini Reviews in Medicinal Chemistry, 2021)
Background: Coronavirus disease 2019 (COVID-19) outbreak was declared as an emerging global public health concern on 30th January 2020. This novel coronavirus (SARS-CoV-2) outbreak was first identified in Wuhan city, China, which soon affected around 185 countries and territories all over the world through various transmission mechanisms. To date, no permanent cure has been found, due to which this pandemic threatens humanity for its very existence. Objective: In light of the rising menace, this review aims at providing collective and prominent information on the current outbreak, covering its origin, structure, transmission, clinical features, potential treatment approaches, and clinical trial details. Methods: The literature published in Scopus and PubMed indexed journals were reviewed, and clinical trial data was retrieved from the ClinicalTrials.gov database. Results: Present review puts forth detailed insights on history, epidemiology, structure, genetic makeup, reservoirs, entry mechanisms, reproduction capacity, pathogenesis, routes of transmission, clinical features, diagnostics, the role of chloroquine in treatment, current promising therapies, and vaccination trials. Conclusion: At present, early detection, isolation of infected patients, and supportive care with a few recently USFDA approved alternative medications are being used as per the standard government guidelines. Due to insufficient availability of proof regarding current therapies to produce therapeutic activity against COVID-19, safety precautions, prevention methods, hygiene maintenance and management therapy with intensive care medicine is the only way to fight this current situation.
Keywords: antimalarial drugs